Metaphorics and intertexts in the key text positions of political media discourse - V. O. Pareshneva (Гуманитарные и юридические исследования)
This article offers an analysis of the contaminated method of metaphorization for the headline set within the political media discourse. Metaphorical models of implementing the manipulative and predictive functions of the title viewed as a strong position of the text are considered as complex formations including intertextuality and precedent elements. The study examines various ways that serve to intensify and improve precedent phenomena used as a source-sphere in translating the author’s axiological space and shaping vectors of interpretation for political articles metatext.The headline is a brief representation of objective and reflexive prognostics, which steers the “correct” perception of the entire text. The examples are based on the method of stratified sampling, with headlines and contexts from recognized online issues “The Telegraph”, “Politico”, “The Guardian” selected, which contain specific metaphorical allusions based on precedent situations and statements. The dominance of a certain metaphorical transference model and the preservation of reminiscences to a specific precedent phenomenon within the text seen as a single interpretation space, as well as in a number of political media discourse texts creates a textual universe or a single narrative that translates a certain type of perception of the image and ideas concerning the actions of the image formation source (political figure).Within the unified metaphorization model, the criteria features of the source-sphere (nuclear areas of comparison) in the areas of schematization and stereotypization of perception, as set by the author in the incoative components (title), there are several types of metaphorical intertextuality (paratextuality, metatextuality, hypertextuality, architectuality) implemented simultaneously.Metaphorics and intertextuality in headlines play a key role in forecasting the perception and the interpretation of the following text, which offers ample opportunities to verbalize subjective evaluation of the described event and has the greatest potential for reflexive verification and further legitimization of the author’s subjective axiological scale. Complex metaphorization offers a basis for a wide range of readers to shape an illusion of reinforcement of the axiologems broadcast by the greater majority of members of a linguo-cultural community, as well as an impression of describing the recipient’s own thoughts.